Impact of crowdfunding, entrepreneurial finance and varieties of entrepreneurial ecosystems after COVID pandemic for rural women - Zhikang Lyu; Natasha Murtaza (PLoS ONE, 2026)
In this paper, we propose an approach to estimate the role of entrepreneurial finance and social capital distribution in crowdfunding (CF) and varieties of entrepreneurial ecosystems after the COVID pandemic for rural women in Pakistan. Primary data were collected from 1,004 rural women. Using SmartPLS, hypotheses were analyzed through partial least squares structural equation modeling. The mainstream tests used for checking the discriminant validity are the Fornell and Larcker Criteria, Heterotrait–Monotrait ratio, Average Variance Extracted, Variance Inflation Factor (VIF), and the factor loadings of each item for each variable. Similarly, the reliability of the data was analyzed through Cronbach’s alpha and composite reliability. The results showed that crowdfunding, social capital distribution, and the variety of an entrepreneurial ecosystem could play a vital role in the entrepreneurial intentions of rural women in Pakistan. Moreover, the distribution of social capital plays a positive role in the variety of the entrepreneurial ecosystem. The study also provides a benchmark pathway for social change for rural women in Pakistan following the COVID-19 pandemic, revealing how various entrepreneurial ecosystems can assist them in achieving their business goals by providing a clear roadmap for crowdfunding (CF).